FAST NEURAL NETWORK FOR GENERALIZED TRIGONOMETRIC TRANSFORMATIONS SYNTHESIS - Liskevych, Oleh; Yatsymirskyy, Mykhaylo (International Journal of Computing, 2014)
The structure of the fast hardware neural network, based on generalized trigonometric transformations algorithm is developed. The network is appointed for optimal by some given criteria transformation selection and synthesis in adaptive digital signal processing system.